Meta Analysis of Entrepreneurial Skill and Entrepreneurial Motivation On Business Performance: Mediating Role Of Strategic Leadership In Sme Sector Of Ethiopia - Dereje Dinsa Negeri; Gada Gizachew Wakijira; Shashi Kant (Research Synergy Foundation, 2023)
As the world economy continues to move towards increased integration, some of the greatest opportunities for MSE will derive from their ability to participate in global market place. It is generally accepted that SMEs are becoming highly important in terms of employment, wealth creation, and the development of innovation. However, there are considerable problem about the quality of management/strategic leadership/ entrepreneurial skill and entrepreneurial motivation in this sector and other issues like weaknesses in innovation, a lack of financial acumen, marketing, entrepreneurial flair, practical knowledge, and human resource management. As a result of this fact, this study will aim to analyze the effects of entrepreneurial skill and entrepreneurial motivation on Business performance, With mediating role of strategic leadership: The case of selected SME Sectors in Guji Zone oromia regional state, Ethiopia. The study was employed a Quantitative research design method by using surveys questionnaire to collect data. The selections of the respondent for this study will random sampling and purposive sampling for SME owners and leaders of both zonal and towns job opportunity creation and skill office and are purposely selected to respond the questionnaires. Since the Zone is so large in size, the researcher will select 5 towns Nagele, Adola, Shakiso, Bore and Haro wachu. A total of 382 respondents will be selected as sample size. Estimating the total population as 2,322 owners and job opportunity creation and skill office leaders in 5 towns, the sample size 382 will be determined by using Yamane (1967) Because of its simplicity to use. The analysis of data is took place by using Classical Linear Regression Model. In this case, the analysis of data involved the use of chi square, correlation and ordinal logistic regression in order to analyze the effects of entrepreneurial skill and entrepreneurial motivation on business performance, with mediating role of strategic leadership. Result indicated that, all variables have positive and significant effect on business performance.